Telemedicine in the Northern Territory: An assessment of patient perceptions in the preoperative anaesthetic clinic. (23rd January 2015) - Roberts, Simon; Spain, Brian; Hicks, Chelsea; London, James; Tay, Stanley
Abstract: Objective: We investigated patient perceptions of a virtual preoperative anaesthesia evaluation clinic linking Royal Darwin Hospital to Katherine Hospital. Design: Descriptive study, cross‐sectional survey. Setting: Regional and rural areas of Northern Territory, Australia. Participants: Sample includes 27 respondents, five Indigenous, 18 non‐Indigenous and four unknown. Interventions: Introduction of a preoperative anaesthesia evaluation clinic. Main outcome measures: We designed a 10‐item, 5‐point Likert scale questionnaire assessing patient perceptions in four domains: (i) technical quality; (ii) perceived efficacy; (iii) affective patient experience; and (iv) patient preference. Qualitative responses are also reported. Results: Twenty‐seven out of 35 patients (77%) completed the questionnaire. Ninety‐eight per cent were in positive agreement on technical quality with a mean score of 1.35 (SD: 0.53); Ninety‐five per cent on perceived efficacy, 1.35 (SD: 0.65); Eighty‐four per cent in negative agreement on affective patient experience (negative perception item), 4.19 (SD: 1.07); Eighty‐one per cent in negative agreement on patient preference (negative perception item), 4.23 (SD: 1.14). There were no significant differences in the answers between Indigenous (five patients) and non‐Indigenous patients (18 patients). Conclusion: Our study confirms the acceptability of telemedicine in the remote assessment of preoperative patients in the Northern Territory, with positive perceptions in all four domains.